The Role of Financial Technology in The Creative Industries in Indonesia - Nono Heryana; Rini Mayasari; Rudi Aprianto (Information System; Universitas Buana Perjuangan Karawang, 2020)
In the modern era, the use of technology is growing rapidly to obtain information and various other electronic services, many people who already use technology, especially the internet to facilitate their work. Seeing the rapid development of the internet has given rise to various innovations, especially financial technology to meet the various needs of the community including access to financial services and transaction processing. Fintech (Financial Technology) is an innovation in the financial sector that refers to modern technology used to transact, check deposit rates, transfer funds, and perform various other financial services. The creative industries are an industry that utilizes the creativity and skills of individuals use as goods of value. The purpose of this study is to determine the role of financial technology and its constraints in the creative industry in Indonesia. The existence of innovation and creativity that arises in the community, making the creative industry is an essential role in the development of a regional economy. The research method used in writing this article is descriptive qualitative. Thus, qualitative research only describes responses to situations or events so that it does not explain causality or do hypothesis testing.